Alternative Payment Models and Patient-Reported Quality of Preparation for Discharge: A Retrospective Longitudinal Study - Sunny C. Lin PhD MS; Julia Adler-Milstein PhD; John M. Hollingsworth MD, MS; Andrew Ryan PhD (Journal of Patient Experience, 2024)
Preparing patients for posthospital care may improve readmission risk. Alternative payment models (APMs) incent hospitals to reduce readmissions by tying payment to outcomes. The impact of APMs on preparation for discharge is not well understood. We assessed whether patient-reported preparation for posthospital care was associated with reduced readmissions, and whether APM participation was associated with improved preparation for posthospital care. We used mixed-effects regression on retrospective (2013–2017) observational data for 2685 U.S. hospitals. We measured patient-reported preparation for posthospital care using the 3-Item Care Transition Measure and readmission using 30-day all-cause risk-adjusted readmissions from Hospital Compare. Participation in accountable care organizations (ACOs), Medical Homes, and Medicare's Bundled Payments for Care Improvement program was obtained from Medicare, the American Hospital Association's Annual Survey, and Leavitt Partner's ACO database. We found that APMs are not associated with improved preparation for posthospital care, even though it was associated with reduced readmissions (Marginal Effect: −0.012 percentage points). This may be because hospitals are not investing in patient engagement. This study has limited insight into causality and reduced generalizability among smaller, rural, and non-teaching hospitals.